Distributive thermometer: A new unary encoding for weightless neural networks - Bacellar, A. T. L.; Susskind, Z.; Villon, L. A. Q.; Miranda, I. D. S.; Araújo, L. S. de.; Dutra, D. L. C.; Breternitz Jr, M.; John, L. K.; Lima, P. M. V.; França, F. M. G. (ESANN 2022 proceedings, 2022)
The binary encoding of real valued inputs is a crucial part of Weightless Neural Networks. The Linear Thermometer and its variations are the most prominent methods to determine binary encoding for input data but, as they make assumptions about the input distribution, the resulting encoding is sub-optimal and possibly wasteful when the assumption is incorrect. We propose a new thermometer approach that doesn’t require such assumptions. Our results show that it achieves similar or better accuracy when compared to a thermometer that correctly assumes the distribution, and accuracy gains up to 26.3% when other thermometer representations assume an unsound distribution.